2013
DOI: 10.1016/j.biopsych.2012.11.027
|View full text |Cite
|
Sign up to set email alerts
|

Sweetened-Fat Intake Sensitizes Gamma-Aminobutyric Acid—Mediated Feeding Responses Elicited from the Nucleus Accumbens Shell

Abstract: Background There is much interest in exploring whether reward-driven feeding can produce druglike plasticity in the brain. The gamma-aminobutyric acid (GABA) system in the nucleus accumbens (Acb) shell, which modulates hypothalamic feeding systems, is well placed to “usurp” homeostatic control of feeding. Nevertheless, it is unknown whether feeding-induced neuroadaptations occur in this system. Methods Separate groups of ad libitum–maintained rats were exposed to daily bouts of sweetened-fat intake, predator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 54 publications
1
15
0
Order By: Relevance
“…medial portions of the dorsal hypothalamus. Importantly, the low level and pattern of locomotor activity observed in this study is similar to that seen with spontaneous waking (Berridge and Foote, 1996) and is substantially below levels seen with behaviourally-activating doses of systemically-administered psychostimulants (Kuczenski et al, 1991, 1997; Segal, 1975; Segal and Kuczenski, 1997) or with AMPH infusion into the nucleus accumbens at doses similar to those used in the current studies (Newman et al, 2013; Schildein et al, 1998). No evidence of stereotypy was observed with either unilateral or bilateral AMPH infusions.…”
Section: Resultssupporting
confidence: 57%
See 1 more Smart Citation
“…medial portions of the dorsal hypothalamus. Importantly, the low level and pattern of locomotor activity observed in this study is similar to that seen with spontaneous waking (Berridge and Foote, 1996) and is substantially below levels seen with behaviourally-activating doses of systemically-administered psychostimulants (Kuczenski et al, 1991, 1997; Segal, 1975; Segal and Kuczenski, 1997) or with AMPH infusion into the nucleus accumbens at doses similar to those used in the current studies (Newman et al, 2013; Schildein et al, 1998). No evidence of stereotypy was observed with either unilateral or bilateral AMPH infusions.…”
Section: Resultssupporting
confidence: 57%
“…Doses used in the intra-tissue infusion studies were based on previous studies demonstrating this dose range elicited robust waking when infused into the medial septal and medial preoptic areas (Berridge et al, 1999) and locomotor-activating and reinforcing effects when infused into the nucleus accumbens (Carr and White, 1983; Gerdjikov and Beninger, 2005, 2006; Newman et al, 2013; Schildein et al, 1998). For CPP studies, systemic doses were used that have been demonstrated to elicit pronounced arousal-promoting actions in the absence of a strong locomotor activation (Berridge et al, 1999; Berridge and Stalnaker, 2002).…”
Section: Methodsmentioning
confidence: 99%
“…Nevertheless, this ‘normal’ μ-OR-mediated regulation could progress to dysregulation if μ-OR activation occurs in the context of a faulty efferent network; for example, if the motivational ‘limiter’ function of the circuitry has been compromised and can no longer hold cortically driven responses in check. Recent findings have begun to suggest that exposure to reward-driven feeding engenders adaptations within PFC terminal fields that could, in principle, result in a blunting of the proposed PFC→AcbSh ‘limiter circuit’ [85]. Rats that had gorged daily on sweetened fat displayed a markedly sensitized feeding response to a low-dose intra-AcbSh challenge of the GABA agonist, muscimol.…”
Section: Cortico–striato–hypothalamic Network Dysfunction In Syndromementioning
confidence: 99%
“…On the output side, both the vmPFC and AIC send direct projections to feedingmodulatory hypothalamic regions (Hurley et al, 1991;Floyd et al, 2001). Additionally, vmPFC (and, to a lesser extent, the AIC) sends strong projections to the nucleus accumbens shell (Vertes, 2004;Reynolds and Zahm, 2005), a site at which profound hyperphagia is elicited by GABA or opiate receptor stimulation (Basso and Kelley, 1999;Newman et al, 2013).…”
Section: Introductionmentioning
confidence: 99%